Hard luck how luck undermines free will and moral responsibility - Levy, Neil, 1967- (Oxford : Oxford University Press, 2011)
The concept of luck plays an important role in debates concerning free will and moral responsibility. Neil Levy presents an original account of luck and argues that it undermines our freedom and moral responsibility no matter whether determinism is true or not.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Fortune; Fortune -- Moral and ethical aspects; Free will and determinism; Responsibility